Discovery of a novel exceptionally potent and orally active Nur77 ligand NB1 with a distinct binding mode for cancer therapy - Jun Chen; Taige Zhao; Wenbin Hong; Hongsheng Li; Mingtao Ao; Yijing Zhong; Xiaoya Chen; Yingkun Qiu; Xiumin Wang; Zhen Wu; Tianwei Lin; Baicun Li; et al. (Acta Pharmaceutica Sinica B)
The orphan nuclear receptor Nur77 is emerging as an attractive target for cancer therapy, and activating Nur77's non-genotypic anticancer function has demonstrated strong therapeutic potential. However, few Nur77 site B ligands have been identified as excellent anticancer compounds. There are no co-crystal structures of effective anticancer agents at Nur77 site B, which greatly limits the development of novel Nur77 site B ligands. Moreover, the lack of pharmaceutical ligands restricts Nur77's therapeutic proof of concept. Herein, we developed a first-in-class Nur77 site B ligand (NB1) that significantly inhibited cancer cells by mediating the Nur77/Bcl-2-related apoptotic effect at mitochondria. The X-ray crystallography suggests that NB1 is bound to the Nur77 site B with a distinct binding mode. Importantly, NB1 showed favorable pharmacokinetic profiles and safety, as evidenced by its good oral bioavailability in rats and lack of mortality, bodyweight loss, and pathological damage at the 512.0 mg/kg dose in mice. Furthermore, oral administration of NB1 demonstrated remarkable in vivo anticancer efficacy in an MDA-MB-231 xenograft model. Together, our work discovers NB1 as a new generation Nur77 ligand that activates the Nur77/Bcl-2 apoptotic pathway with a safe and effective cancer therapeutic potency.